A Systematic Review and Meta-Analysis of Influences of Chronic Kidney Disease on Patients after Percutaneous Coronary Intervention for Chronic Total Occlusions. (22nd February 2023) - Wu, Weifei; Gao, Menghan; Wu, Xu
Abstract : Objective. Chronic kidney disease (CKD) is a clinical collective term for kidney disease with glomerular filtration rate GFR < 60  mL/min for more than three months due to various factors and is usually associated with coronary heart disease and is also an independent risk factor for coronary heart disease. This study is aimed at systematically reviewing the influence of CKD on the outcomes of patients after percutaneous coronary intervention (PCI) for chronic total occlusions (CTOs). Methods. The Cochrane Library, PubMed, Embase, China biomedical literature database (SinoMed), China National Knowledge Infrastructure, and Wanfang database were searched for case-control studies on the influence of CKD on outcomes after PCI for CTOs. After screening the literature, extracting data, and evaluating the quality of literature, RevMan 5.3 software was used for meta-analysis. Results. There were 11 articles with a total of 558, 440 patients included. Meta-analysis results indicated that left ventricular ejection fraction (LVEF) level, diabetes, smoking, hypertension, coronary artery bypass grafting, angiotensin converting enzyme inhibitor (ACEI)/angiotensin receptor blocker (ARB), β -blockers, age, and renal insufficiency were the factors affecting outcomes after PCI for CTOs [risk ratio and 95% confidence interval were: 0.88 (0.86, 0.90), 0.96 (0.95, 0.96), 0.76 (0.59, 0.98), 1.39 (0.89, 2.16), 0.73 (0.38, 1.40), 0.24 (0.02, 3.9), 0.78 (0.77, 0.79), 0.81 (0.80, 0.82), and 1.50 (0.47, 4.79)]. Conclusion. LVEF level, diabetes, smoking, hypertension, coronary artery bypass grafting, ACEI/ARB, β -blockers, age, renal insufficiency, etc. are important risk factors for outcomes after PCI for CTOs. Controlling these risk factors is of great significance for the prevention, treatment, and prognosis of CKD.